Antiretroviral therapy 2007, new concepts and lessons learned - Redfield, Robert (Henry Stewart Talks, 2007)
Data from recent past about AIDS, HIV life cycle and mechanisms of action of antiretroviral agents, Nucleoside-nucleotide reverse transcriptase inhibitors (NRTIs/NtRTIs): potency, pharmacokinetics and adverse effects, Non-nucleoside reverse transcriptase inhibitors (NNRTIs), Protease inhibitors (PIs), Cell entry inhibitors, Initiation of antiretroviral therapy in the naive patient, Health authorities' guidelines for initial therapy, Key factors for improved durability, Cell cycle and effect of antiviral agents, Risks of early treatment, New directions in antiretroviral therapy
Archived at 2018/10/28